Adenosine Deaminase and Systemic Immune Inflammatory Index—A Biomarker Duet Signature of Pulmonary Tuberculosis Severity - Ioan Anton Arghir; Oana Cristina Arghir; Marina Ruxandra Otelea; Iulia Tania Andronache; Ileana Ion (Medicina)
Background and Objectives: The role of adenosine deaminase (ADA) in pulmonary tuberculosis (PTB) remains insufficiently defined in advanced forms of disease. Likewise, the systemic immune inflammatory index (SII) has not been validated in severe PTB. This 6-year prospective observational study aims to evaluate biomarker signatures of serum ADA and SII. Materials and Methods: According to the PTB case definition, 232 adult patients were divided into group 1, with a positive bacteriologic exam (n = 168), and group 2, without bacteriological confirmation (n = 64). ADA serum levels were compared by age, gender, nutritional status, morphologic and bacteriological pattern of PTB lesions, survival status, along with serum levels of other inflammatory biomarkers. All patients with comorbidities, interfering with the level of ADA, were excluded to avoid bias. Results: A total cohort of 208 PTB adults, aged 54.37 ± 14.365 years, included 156 males. The overall mortality was 11.53%. Death occurred after a mean interval of 1.63 ± 3.228 months after PTB diagnosis. ADA serum mean levels were 32.94 ± 9.146 IU/L, significantly higher in G1 (p = 0.002), in patients with delayed diagnosis of PTB (p = 0.000), with lung cavitation (p = 0.003), and death as a poor outcome (p ˂ 0.02). SII had a mean value of 1752.226 ± 2704.150, significantly increased in bacteriologically confirmed PTB cases (p = 0.018), delayed diagnosis (p = 0.002), cavitary advanced pulmonary tuberculosis (APT) (p = 0.002), and deceased (p = 0.003). Both an ADA cut-off elevated risk value of over 30 IU/L and SII of over 902 were fulfilled by 73 patients, with 2.10 higher risk of advanced PTB (p = 0.006) and 4.49 higher risk of mortality (p = 0.000). Conclusions: Serum ADA and SII are recommended as predictors of advanced and severe pulmonary TB. These findings indicate that ADA and SII, when elevated together, delineate a high-risk PTB phenotype with greater disease severity and early mortality. The combination offers a pragmatic, biomarker-based approach to risk stratification in PTB.